2019
DOI: 10.1021/acs.langmuir.9b02651
|View full text |Cite
|
Sign up to set email alerts
|

pH and Redox Dual-Stimulated Wormlike Micelles Based on Cystamine and Conventional Anionic Surfactant

Abstract: Redox-responsive soft materials have attracted considerable concerns throughout the last few decades. Herein, we report the preparation of dual-stimulated wormlike micelles (WLMs) based on N,N,N′,N′-tetramethylcystamine dihydrochloride (TMCDD) and a conventional anionic surfactant, sodium dodecyl sulfate (SDS). The WLMs can be reversibly switched on and off by adjusting pH, resulting from the reversible protonation of TMCDD. Moreover, the WLMs can be destroyed by a redox reaction after addition of dithiothreit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Related research , has shown that the variation of the solution pH would change the CMC of the surfactant; the number of micelles formed in the solution would also change at a constant concentration. In addition, the micellar structure of surfactant molecules will also change as pH varies. Therefore, it is assumed that the variation in micelle structure is the main reason for the change in surfactant DR effect with the pH value of the solution. To better clarify the influence of solution pH on surfactant micelles and further understand the influencing mechanisms of pH value on DR performance of surfactant solutions, the CMCs of surfactant solutions under different solution pH values was also experimentally investigated, and the results are shown in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Related research , has shown that the variation of the solution pH would change the CMC of the surfactant; the number of micelles formed in the solution would also change at a constant concentration. In addition, the micellar structure of surfactant molecules will also change as pH varies. Therefore, it is assumed that the variation in micelle structure is the main reason for the change in surfactant DR effect with the pH value of the solution. To better clarify the influence of solution pH on surfactant micelles and further understand the influencing mechanisms of pH value on DR performance of surfactant solutions, the CMCs of surfactant solutions under different solution pH values was also experimentally investigated, and the results are shown in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Because of these viscoelastic properties, WLMs find application as drag reducing agents, in enhanced oil recovery, in home and personal care products, and more. 16−18 More interestingly, WLMs can be made responsive to external stimuli such as light, 19−24 temperature, 23,25,26 pH, 23,27−31 CO 2 , 21,32−34 redox reaction, 35,36 and even a combination of stimuli. 21,23,37 These systems, called "smart" WLMs, 38 have a common feature in that the stimulus causes a drastic change in the size (contour length) of the WLM chains.…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, WLMs can be made responsive to external stimuli such as light, temperature, ,, pH, , CO 2 , , redox reaction, , and even a combination of stimuli. ,, These systems, called “smart” WLMs, have a common feature in that the stimulus causes a drastic change in the size (contour length) of the WLM chains. In turn, the rheological properties of the WLM solution such as its zero-shear viscosity (η 0 ) or its relaxation time (τ R ) can be varied by orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%